2007
DOI: 10.1161/circulationaha.106.647248
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced External Counterpulsation Inhibits Intimal Hyperplasia by Modifying Shear Stress–Responsive Gene Expression in Hypercholesterolemic Pigs

Abstract: Background-Enhanced external counterpulsation (EECP) is a circulation assist device that may improve endothelial dysfunction by increasing shear stress. Chronic exposure of vascular endothelial cells and vascular smooth muscle cells to relatively high physiological shear stress has antiproliferative and vasoprotective effects. The present study hypothesizes that EECP inhibits intimal hyperplasia and atherogenesis by modifying shear stress-responsive gene expression. Methods and Results-Thirty-five male pigs we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
110
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 99 publications
(119 citation statements)
references
References 28 publications
8
110
0
1
Order By: Relevance
“…These findings are consistent with pG z activation of the Akt/PI3K pathway as a stimulus to eNOS activity, the latter via induced pulsations with circumferential stretch on the vascular endothelium. Our results also agree with in vitro endothelial cell culture findings of other investigators, who showed that pulsatile shear stress upregulates eNOS activity via the Akt/PI3K pathway (32,41,45,57).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…These findings are consistent with pG z activation of the Akt/PI3K pathway as a stimulus to eNOS activity, the latter via induced pulsations with circumferential stretch on the vascular endothelium. Our results also agree with in vitro endothelial cell culture findings of other investigators, who showed that pulsatile shear stress upregulates eNOS activity via the Akt/PI3K pathway (32,41,45,57).…”
Section: Discussionsupporting
confidence: 93%
“…In humans, descent of the dicrotic notch of digital and aortic pulse waves has been observed with nitrate and albuterol administration, as well as with exercise (10,26,29,39,42,46). This finding is mediated through the action of NO, since inhibition of NO synthesis with N G -nitro-L-arginine methyl ester (L-NAME) or N G -monomethyl-L-arginine prevents descent of the dicrotic notch after acetylcholine or albuterol administration in rabbits and humans, respectively (26, 52).Our purpose was to assess whether pG z applied to rats serves as a means of producing endothelial-dependent vasodilatation and to test whether such an effect is mediated, in part, via the well-known shear stress induced Akt/phosphatidylinositol 3-kinase (PI3K) pathway for NO production (13,55,57). …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…4,8,10 Although changes in aortic and coronary hemodynamics have been proposed as primary hypotheses for the central changes after EECP, just a few studies have focused on the peripheral hemodynamics. [11][12][13][14] More specifically, acute blood flow patterns created by cuff compressions and their impact on peripheral endothelial function have not been studied in humans. The present study aims to determine if there is any acute peripheral vascular adaptation after a single 45-min session of EECP.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, animal and human studies, [11][12][13] and mathematical models 14 have shown that EECP produces an increased retrograde blood flow and blood flow velocity in the lower extremities. Interestingly, there are some contradictory results when measuring endothelial function after retrograde flow.…”
Section: Introductionmentioning
confidence: 99%